Draft horse (Percheron) in halter; with Chester Rubel [? --or Charles Myszka] - Frank Aston::::::photographer::: (1915)
Draft horse (Percheron) in halter; with Chester Rubel [? --or Charles Myszka] Published in Polytechnic J. (1915, p.57) with caption 'A long sloping shoulder insures elasticity of movement.' Another image of this horse (same photo session) was published in Bulletin (series 4 no.1, 1915-16) and in Polytechnic J. (1915, p.56)